(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
This study examines the meaning of the action verb "eat" in Sundanese through a semantic approach. The aim is to describe the variations in meaning and context of the verb "eat" in Sundanese. Data was collected through observations of short video content on social media platforms such as YouTube and TikTok. While the verb "eat" generally means putting food into the mouth, in the context of Sundanese, this activity carries more complex and diverse nuances. The results show that the verb "eat" in Sundanese has a rich variety of lexicons, such as dahar, neda, tuang, emam, lebok/lelebok, hakan/barang hakan, jajablog, daang, madang, cacatrek, gagares, nyatu, lolodok, botram, bancakan, papahare, ngalimed, and ancin. Each lexicon is used in different contexts, reflecting levels of politeness, situations, or figurative meanings. This research provides an in-depth understanding of how the verb "eat" not only represents a physical activity but also embodies cultural and social values within Sundanese society.